A Comprehensive Narrative Review on the Hazards of Bee Honey Adulteration and Contamination - Ionela-Daniela Morariu; Liliana Avasilcai; Madalina Vieriu; Vasile Valeriu Lupu; Ileana Ioniuc; Branco-Adrian Morariu; Ancuța Lupu; Paula-Cristina Morariu; Oana-Lelia Pop; Vladut Mirel Burduloi; Iuliana Magdalena Starcea; Laura Trandafir (Journal of Food Quality)
Honey bees are renowned for producing a remarkable substance known as bee honey, which stands as a functional food celebrated for its numerous health benefits. This natural wonder possesses a spectrum of advantageous properties, including anti-inflammatory, antioxidant, analgesic, antibacterial, and wound-healing qualities. However, in our modern era of heightened utilization of bee products, a new and pressing global health concern has emerged—the contamination of honey with pesticides, antibiotics, microorganisms, and heavy metals. The consumption of beekeeping products containing pesticide residues has been linked to a range of health issues, including genetic malformations, cellular degradation, allergic reactions, and even potential carcinogenic effects. Troublingly, documented cases exist of botulism in newborns resulting from the ingestion of contaminated honey. Additionally, the use of antibiotics in beekeeping practices has been associated with the concerning emergence of antibiotic resistance. This comprehensive review sheds light on the substantial consequences of honey contamination for human health. It underscores the urgent need for the establishment of a rigorous monitoring system, the validation of minimum acceptable pollutant levels, and, at the very least, the regulation of maximum residue limits for bee products, with a particular emphasis on bee honey.